Conception of developing ethnomedicine specialized nursing in ethnomedicine hospitals (民族医医院发展民族专科化护理的构想) - GONG Shanhong (龚珊鸿); HU Xiaoyue (胡晓玥); LI Xuemei (李雪梅); BIN Caiqin (宾彩琴) (Association of Integrative Nursing, 2023)
This paper reviewed the development status of Traditional Chinese Medicine specialized nursing and the shortcomings of the current development of specialized nursing, and analyzed the ideas of ethnomedicine specialized nursing in ethnomedicine hospitals in the following aspects: Strengthening the research of ethnomedicine nursing theory and gradually improve the theoretical system of disciplines; Strengthening continuing education and training for medical and nursing talents; Selecting the dominant diseases of each department of ethnomedicine hospitals and formulate the nursing plan of ethnomedicine specialty; Formulating evaluation standards for the nursing efficacy of ethnomedicine treatment and the standards of characteristic nursing techniques; Paying attention to the cultural construction of hospitals and departments, and establishing an emotional bond between medical staff and patients. (本文探讨中医专科护理的发展现状以及现阶段专科护理发展的不足之处, 提出民族医医院发展民族专科化护理的构想: 加强民族医护理理论的挖掘, 逐步完善学科理论体系; 加强继续教育培训力度, 培养民族医高精尖护理人才; 遴选民族医医院各科室优势病种, 制定壮医专科的护理方案; 制定民族医病种护理疗效评价标准以及特色护理技法的操作规范; 注重医院、科室文化建设, 建立医护患三者之间的情感纽带。)